Electron density profile of the F-region near the equatorial anomaly crest during moderate solar activity - Rhazali Z.A.; Zain A.F.M. (Institute of Electrical and Electronics Engineers Inc., 2023)
The ionospheric F-layer profiles over Parit Raja (Lat. 1°52'N, Long. 103°48'E, Magnetic dip 14.3°) are observed for 5 days; from January 14 to January 18, 2005, a period in moderate solar epoch. Analyses show that the ionospheric profiles development and decay are accompanied by the rise and fall in the height associated to the profile density. The profile peak reaches its highest level during noon and lowest during pre-sunrise, under normal condition. Mixed profiles are observed during disturbed condition. The density size expands but reduction in peak height is observed. In addition, the electron density profile can also be a pre-cursor to the occurrence of spread-F. © 2014 IEEE.